TRIASSIC CARBONATE AND EVAPORITE SEDIMENTATION IN THE IONIAN ZONE (WESTERN GREECE): PALAEOGEOGRAPHIC AND PALAEOCLIMATIC IMPLICATION - Getsos, K.; Pomoni-Papaioannou, F.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2018)
The Triassic is considered a crucial interval because during that time huge areas in our planet suffered an intense, long lasting, period of aridity, which favored the formation of worldwide evaporitic bodies. During the Triassic, great volumes of evaporites were formed in the Ionian basin (Western Greece). On the surface chaotically textured gypsum, surrounded by dolomitic breccias of solution-collapse origin, appears. Sedimentological and diagenetical data proposed that these salt bodies were formed in an intertidal to supratidal environment. Although halite suggests precipitation under long-term arid conditions, clay film intercalations reveal intervals of short term humid conditions. During arid periods sabkhas prevailed and brines were of marine origin. Instead, during humid intervals brines were modified by meteoric water and stormy episodes could be responsible for the transportation of clay-sized material, from the low relief surrounding terrains, into the evaporative basin. Death and burial of cyanobactehal population during storm events could be responsible for the enrichment of clayey layers in carbonaceous material. The co-existence of halite and clays in the Ionian evaporitic sequence imposes a complicated climate, possibly periodically and seasonally controlled. The impact of the precession of the equinoxes plus the palaeogeographical position dominates the local climate. The insolation over the Triassic Ionian basin and nearby sea and land areas is a crucial factor. Climate responses to gradual insolation forcing with an ocean land atmosphere feedback mechanism. The desert / monsoonal dominated climatic model seems to be most proper for the explanation of the existing lithologigal record.